Seed weevil released to control milk thistle - R Hawkes; L Andres; P Dunn (California Agriculture, 1972)
Milk thistle, Silybum marianum (L.) Gaertn., is a widespread weed of increasing importance on range-land, ditch banks, highway and railroad right-of-ways, and wasteland in California. Although reported to be a biennial, it grows mainly as a winter annual, generally invading disturbed and overgrazed land. The plant reproduces only by seed.